Proposta de avaliação de riscos em prensas hidráulicas com lógica Fuzzy - SLUCE, Patrícia (Universidade Federal do Pará, 2021)
The aim of this study was to evaluate the safety level of industrial machines, in particular hydraulic press. The dissertation used hydraulic presses as the object of study. The research instruments used were machine safety analyzes based on normative items preestablished in ABNT NBR: 12100, possible accidents that these machineries can cause. The results show that hydraulic presses cause many accidents, in some situations dying. Through Annex B of ABNT NBR 14153: 2013, there are 4 risk categories for machinery, the greater the degree of risk, the more unsafe the machine is. The appraiser's experience is very important to analyze the machine and reach the level of risk level before and after the adjustment. Finally, it appears that the machine analyzed in this study was at risk level 3, after analysis and adaptations the same machine was at risk level 1, totally acceptable to maintain the operator's safety level.